Telemonitoring alat fisioterapi pasien pasca stroke berbasis Internet of Things (IoT) - Lis Diana Mustafa; Azam Muzakhim Imamuddin; Yoyok Heru Prasetio (JURNAL ELTEK, 2021)
Stroke Transient Ischemic Attack (TIA ) adalah kondisi stroke ringan. Stroke ringan diakibatkan oleh berkurangnya suplai darah menuju otak. Kelumpuhan disebabkan oleh kurangnya aliran darah ke otak, sehingga sisi tubuh akan mengalami kelumpuhan terutama pada siku dan lutut. Fisioterapi pada pasien pasca stroke ringan dilakukan dengan metode terapi gerakan antara lain seperti penggunaan alat bantu fisioterapi pasien pasca stroke menggunakan sensor MPU6050 melalui media transmisi Bluetooth. Sistem rancangan ini membantu latihan pada pasien berbentuk sensor MPU6050 yang digunakan untuk mendeteksi sudut serta banyaknya gerakan rehabilitasi pasien pasca stroke. Sensor gyroscope menghasilkan deteksi sudut pada siku sebesar 150 dan sudut pada lutut sebesar 135 . Data yang didapatkan diproses oleh arduino nano menggunakan metode I2C. Penelitian ini bertujuan untuk merancang alat bantu fisioterapi pasien pasca stroke berbasis mikrokontroler guna memperoleh hasil yang maksimal karena bentuk alat ini yang portable. Stroke Transient Ischemic Attack (TIA) is a mild stroke condition that can be caused by reduced blood supply to the brain due to blocked blood vessels. Lack of blood flow to the brain can cause paralysis, usually only on one side of the body such as the elbows and knees. Physiotherapy in post-stroke patients is carried out using movement therapy methods, including elbow and knee flexion. Currently, patients come to the therapist or vice versa to perform therapeutic movements, so a telemonitoring system for post-stroke patient physiotherapy tools is made using the MPU6050 sensor which is connected to ESP 232 and the internet network and can be monitored by therapists and clinic admins where the therapy is done. This system helps monitor elbow and knew flexion exercises using the MPU6050 sensor which is used to detect the angle and number of rehabilitation movements of post-stroke patients. . From the results of testing the accuracy of this sensor is able to detect the angle of elbow movement from 00-1500 and knee flexion angle of 00-1350 by 99%.The telemonitoring application for physiotherapy tools for post-stroke patients based on Android is equipped with a therapist menu so that the number of movements and the average angle of movement of the knees and elbows can be monitored by the therapist, this tool can also be used anywhere and anytime due to the portable form of this tool.